Achieving cervical cancer elimination: The simulated impacts of HPV vaccination and transitioning from liquid-based cytology to HPV-based screening test. - Nur Zahirah Balqis-Ali; Jailani Anis-Syakira; Weng Hong Fun; Zakiah Mohd Said; Shazimah Abdul Samad; Norhaslinda Zainal Abidin; Jafri Zulkepli; Norazura Ahmad; Mohd Norazam Mohd Abas; Chee Meng Yong; Siti Norbayah Yusof; Nur Adila Daud; et al. (PLoS ONE)
The Ministry of Health Malaysia aims to fully replace liquid-based cytology (LBC) with Human Papillomavirus (HPV) tests and increase the screening coverage from a baseline of 25% to 40% by 2023, followed by a 10% yearly increment until 70% coverage. This transition requires proper planning, including the number of tests needed and budget allocation. This study aims to simulate different transition strategies involving the shift from LBC to HPV testing with expanded screening coverage to predict their impact on cervical cancer elimination in Malaysia. A system dynamics model was developed to simulate the transition from LBC to HPV testing and HPV vaccination coverage in Malaysia. The dynamic model utilised local epidemiological data, published research, and expert opinion when data was unavailable. The simulation showed that a combination of high HPV vaccination coverage and transitioning fully to five-yearly HPV testing by 2030, coupled with a 70% screening uptake by 2040, would accelerate cancer elimination in Malaysia by 18 years with an estimated screening cost of MYR1.81 billion equivalent to USD 411 millions compared to the baseline of using LBC as the primary screening method (MYR1.39 billion, USD 315 millions). Sustained, it would lead to averting 6,000 new cancer cases by 2070. Alternatively, conducting HPV screenings twice before age 50 would advance cervical cancer elimination by 14 years and prevent approximately 1000 new cases by 2070, with an estimated cost of MYR1.13 billion equivalent to USD 257 millions. A delay in achieving the full transition prolonged the elimination more than a delay in increasing the screening coverage. In all scenarios, yearly vaccination of 90% of girls age 13 is crucial to achieving elimination. In the Malaysian context, where HPV vaccination coverage has reached considerable levels, the evidence advocates for a full transition from LBC to HPV testing, ideally by 2030. While expanding screening coverage remains a critical factor in this endeavour, the findings unequivocally endorse prioritising the transition process. Trial registration: Trial registration number: NMRR ID-22-00187-DJU.